Analysis of characteristic aromas of buckwheat with different germplasm using gas chromatography–mass spectrometry combined with chemometrics and multivariate statistical analysis - Yunlong Li; Jianan Wei; Siyi Zhu; Xiaoli Zhou; Yiming Zhou; Minglong Wang (Food Chemistry: X, 2024)
In this study, the volatile components in 40 samples of Tartary buckwheat and common buckwheat from 6 major producing areas in China were analyzed. A total of 77 volatile substances were identified, among which aldehydes and hydrocarbons were the main volatile components. Odor activity value analysis revealed 26 aromatic compounds, with aldehydes making a significant contribution to the aroma of buckwheat. Seven key compounds that could be used to distinguish Tartary buckwheat from common buckwheat were identified. The orthogonal partial least squares-discriminant analysis was effectively used to classify Tartary buckwheat and common buckwheat from different producing areas. This study provides valuable information for evaluating buckwheat quality, breeding high-quality varieties, and enhancing rational resource development.